“Types of the Russia Peoples” in the illustrations of the 1870s in the “Niva” magazine - Anna E. Zhabreva (Историческая этнология, 2025)
The subject of the study are illustrations from the Niva magazine, popular in the Russian Empire, that were published in the first decade of its existence (the 1870s). The educational tasks set by the publisher A.F. Marx were implemented in cross-cutting long-term themes – history and culture, geography and wildlife, scientific discoveries, current events in the country and abroad. An important area of the publication’s work in the context of multinational and multi-confessional Russia was the theme of the culture and life of the peoples of the country. Interest in the material and spiritual culture of the peoples of Russia was prepared by academic expeditions of the 18th century, the organization of the First Ethnographic Exhibition of 1867 and fundamental publications. The Niva magazine was engaged in the popularization of that topic among the population. It systematically published articles and engravings describing the geographical location, climate, way of life, and material culture of different peoples. It order to do that, reputable authors were involved – writers, travelers, and artists. Each material included an engraving that depicted one or a few representatives of the people described. In the early years, the main source of illustrations was the album “Ethnographic description of the peoples of Russia” by G.-T. Pauly, but new drawings from life or photographs were also created. The article examines the main sets of ethnographic illustrations that depict traditional clothing. Their significance as a pictorial source is analyzed. At the end of the article, a list of 108 ethnographic illustrations published in the Niva magazine in 1871–1880 is attached.